ZC-CG-CDBA CMOS Realization and Frequency Agile Filter Application - Alaybeyoglu, Ersin; Kuntman, Hakan; Guney, Arda (IEEE, 2013)
ZC-CG-CDBA (Z copy controlled gain current differencing buffered amplifier) is a new current mode active element, published recently. ZC-CG-CDBA CMOS realization and filter application are presented in this paper. The filter center frequency is controllable with the ECCII (electronically controllable second generation current conveyor). BSIM3 0.18 mu m level-7 SPICE parameters are used in the simulations.
Keywords: ZC-CG-CDBA; ECCII; CCIII; OF-THE-ART; Engineering; Telecommunications